Catalytic activity enhancement of sulfated metal oxide by doping Co on MIL-100(Fe) for esterification. (15th February 2023) - Li, Hui; Wang, Tianyu; Wang, Yangyang; Liu, Fengsheng; Li, Yan; Wang, Yunpu; Guo, Min; Li, Guoning; Ma, Xiaoling
Graphical abstract: Highlights: MIL-100(Fe) is successfully doped with cobalt (Co) and used for stable solid acid synthesis. Doped Co aggrandizes the catalyst surface area and enhance acid intensity and amount. The catalytic stability of solid acid is increased by 20 % with doping Co. Activation energy and pre-exponential factor are calculated for esterification. Abstract: Sulfated metal oxides are widely used in catalyzing esterification for biodiesel production due to their low corrosivity and easy separation. While, the catalytic stability is still a challenge on account of active site leaching during successive batch experiments. To this end, the typical metal organic frameworks, MIL-100(Fe) doped with Co was adopted to load ammonium sulfate ((NH4 )2 SO4 ) for stable heterogeneous acid preparation, which was employed to catalyze the esterification of methanol and oleic acid. Influence of preparation factors of (NH4 )2 SO4 loading amount and activation temperature on catalytic activity were initially evaluated. Furthermore, to elucidate the effect of Co doping, catalysts were characterized by TG, XRD, FTIR, nitrogen adsorption–desorption, Py-FTIR, XPS, SEM and NH3 -TPD. Results indicated that the maximum esterification conversion of 92.56 % was achieved by MS(Fe/Co) with molar ratio of methanol to oleic acid of 8:1 and catalyst amount of 8 wt% at 70 °C in 2 h. In comparison to MS(Fe), Co doping significantly improved the stability, where the catalytic activity of MS(Fe/Co) was increased by 20 % at the fifth cycle. The activation energy and pre-exponential factor of esterification catalyzed by MS(Fe/Co) were also calculated as 42.06 kJ/mol and 5.24 × 10 5 min −1 . This study provides a feasible way to enhance the catalytic stability of heterogeneous acid for biodiesel production.